Introduction to applied statistics - Lentner, Marvin (Prindle, Weber & Schmidt, 1975)
This text is aimed at students in medicine, biology and the social sciences as well as those planning to specialize in applied statistics. It covers the basics of the design and analysis of surveys and experiments and provides an understanding of the basic principles of modeling and inference.